The Effects of Arousal and Approach Motivated Positive Affect on Cognitive Control. An ERP Study - Cudo, Andrzej; Francuz, Piotr; Augustynowicz, Paweł; Stróżak, Paweł (Frontiers in Human Neuroscience, 2018)
A growing body of research has demonstrated that affect modulates cognitive control modes such as proactive and reactive control. Several studies have suggested that positive affect decreases proactive control compared to neutral affect. However, these studies only focused on the valence of affect and often omitted two of its components: arousal and approach motivation. Therefore, we designed the present study to test the hypothesis that cognitive control modes would differ as a function of arousal and approach motivated positive affect. In our study, we used an AX-continuous performance task (AX-CPT), commonly used to examine shifts in proactive and reactive control. We also measured P3b, contingent negative variation (CNV), N2 and P3a components of event-related brain potentials (ERPs) as indicators of the use of cognitive control modes. The findings of the present study demonstrated that approach motivated positive affect modified only the P3b and the CNV without effects on the N2 and P3a components. However, arousal induced by pictures modified P3b, CNV and N2 amplitudes. Specifically, the P3b amplitude was larger, and CNV amplitude was less negative in the high than in the low-approach motivated affect. In contrast, the P3b amplitude was larger and both the CNV and N2 amplitudes more negative in low- compared with high-arousal conditions. These ERP results suggest that approach motivated positive affect enhanced proactive control with no effect on reactive control. However, arousal influenced both proactive and reactive control. High arousal decreased proactive control and increased reactive control compared to low arousal. The present study provides novel insights into the relationship between affect, specifically, arousal and approach motivated positive affect and cognitive control modes. In addition, our results help to explain discrepancies found in previous research.